2014
DOI: 10.1002/2013wr014282
|View full text |Cite
|
Sign up to set email alerts
|

Urban recharge beneath low impact development and effects of climate variability and change

Abstract: Understanding low impact development (LID) planning and best management practices (BMPs) effects on recharge is important because of the increasing use of LID BMPs to reduce storm water runoff and improve surface-water quality. LID BMPs are microscale, decentralized management techniques such as vegetated systems, pervious pavement, and infiltration trenches to capture, reduce, filter, and slow storm water runoff. Some BMPs may enhance recharge, which has often been considered a secondary management benefit. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 60 publications
0
50
0
2
Order By: Relevance
“…LID collects runoff close to the source in small structures, generally in urban areas. While costs can be modest, individual LID projects infiltrate relatively little:~10 3 m 3 /yr (~1 ac-ft/yr) (Stephens et al, 2012;Grebel et al, 2013;Newcomer et al, 2014;Bhaskar et al, 2016;Chen et al, 2016). Regional spreading grounds infiltrate excess surface and/or recycled water from large regions, collecting and routing water with dams and other large infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…LID collects runoff close to the source in small structures, generally in urban areas. While costs can be modest, individual LID projects infiltrate relatively little:~10 3 m 3 /yr (~1 ac-ft/yr) (Stephens et al, 2012;Grebel et al, 2013;Newcomer et al, 2014;Bhaskar et al, 2016;Chen et al, 2016). Regional spreading grounds infiltrate excess surface and/or recycled water from large regions, collecting and routing water with dams and other large infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the benefits of LIDs. For example, Newcomer et al (2014) used a numerical model to demonstrate the benefits of LIDs, in particular of an infiltration trench, on recharge and local groundwater resources for future climate scenarios. In another paper, Berardi et al (2014) demonstrated how green roofs may contribute to the development of more sustainable buildings and cities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the HYDRUS software suite (Šimů nek et al, 2008) has been widely used in the literature for the description of the hydraulic behavior of green roofs (Hilten et al, 2008;Li and Babcock, 2015;Newcomer et al, 2014;Palla et al, 2009), with excellent agreement between numerical simulations and experimental data. Newcomer et al (2014) investigated the effects of LIDs on recharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the benefits of LIDs. For example, Newcomer et al (2014) used a numerical model to demonstrate the benefits of LIDs, and an infiltration trench in particular, on recharge and local groundwater resources for future climate scenarios. In another paper, Berardi et al (2014) demonstrated how green roofs may contribute to the development of more sustainable buildings and cities.…”
Section: Introductionmentioning
confidence: 99%